Analisis Kekuatan Konstruksi Pada Alat Angkat Kapasitas 500 Kg Menggunakan Software Comsol Multiphysics - Lukas Kano Mangalla; Samhuddin (Piston: Jurnal Teknologi, 2021)
Lifting equipment is a tool that can alleviate human tasks in terms of the removal objects that have a weight beyond human ability. Mechanical Engineering laboratory of Halu Oleo University (UHO) has lifting equipment with 500 Kg capacity, but construction of this model is not stable and faltered when lifting the weights. This study aim to improve the ability of this equipment for several purposes as well as to produce a draft model of lifting equipment more powerful, economical and has a good aesthetic design. This study was a static load simulation model using COMSOL Multiphysics. Three variations model (model 1, model 2 and model 3) of the construction were simulated with 500 kg of loads. Power stress distributions on the support constructions is the main point in this research for the powerful and useful construction. Furthermore, the good aesthetic designs the important parameter involving on this models. Result of this study shows that the portable crane existing on the Mechanical laboratories needs some improvements on construction, model and aesthetics for 5000kg loads. Model 3 has more powerful and economically construction as well as better aesthetic value than another models investigated.